In Pursuit of the "Full Ride": American Athletic Scholarships and Mobility, Sport and Childhood in Canada - Dyck, Noel (Anthropologica, 2022)
This paper examines the pursuit by Canadian youths of athletic scholarships offered by American colleges and uni- versities, situating their individual efforts within longstanding family projects of child rearing as well as the operations of local sport organizations. Asking why and how the prestige attached in Canada to American athletic scholarships continues to be upheld despite ample evidence of problems associated with this means of obtaining an undergraduate education, the analysis focuses upon the ways in which Canadian youth athletes in the U.S., parents, coaches and college officials play their respective parts in sustaining a distinctive form of coming of age.